2021
DOI: 10.1186/s43044-021-00142-z
|View full text |Cite
|
Sign up to set email alerts
|

The combined role of NT-proBNP and LV-GLS in the detection of early subtle chemotherapy-induced cardiotoxicity in breast cancer female patients

Abstract: Background Chemotherapeutic agents have many side effects; among them is cardiotoxicity. Ejection fraction fails to detect the subtle alterations of left ventricular (LV) function; that is why there is a need for a more sensitive tool. The aim is to detect subclinical LV systolic dysfunction after chemotherapeutic treatment, using NT-BNP plasma level as well as speckle tracking echo-global longitudinal strain (STE-GLS). Seventy-four asymptomatic, non-metastasizing breast cancer female patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…DOX-induced molecular alterations in the cardiac muscle could still occur in clinically asymptomatic patients, as the functional impact can be too subtle to detect (Sulaiman et al 2021 ), leading to a progressive weakening of the heart muscle which may appear much later in life. Strategies for the prevention of DOX-induced cardiotoxicity are already being used in oncological patients.…”
Section: Discussionmentioning
confidence: 99%
“…DOX-induced molecular alterations in the cardiac muscle could still occur in clinically asymptomatic patients, as the functional impact can be too subtle to detect (Sulaiman et al 2021 ), leading to a progressive weakening of the heart muscle which may appear much later in life. Strategies for the prevention of DOX-induced cardiotoxicity are already being used in oncological patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, due to advances in cancer treatment and early detection strategies, the mortality rates of cancer have significantly declined ( 1 ). Studies have shown that in the next 10 years, long-term cancer survivors are expected to increase by about 30% ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical observational cohort study examining NT-proBNP and echocardiography in 74 patients undergoing chemotherapy for breast cancer, there was a strong association between increased NT-proBNP levels and decreased LV-GLS in identifying cardiotoxicity. The results of the study showed good sensitivity and specificity [103]. The relative reduction of LV-GLS, the relative elevation of NT-proBNP 6 weeks after the first chemotherapy dose…”
Section: Proteomics Combined With Echocardiographymentioning
confidence: 86%